PENERAPAN PERANGKAT PEMBELAJARAN MODEL QUANTUM LEARNING TERHADAP HASIL BELAJAR SISWA KELAS X SMA KARTIKA XIII-1 AMBON - Adhar Amir; S I. A Salmanu; Ine Arini (Program Studi Pendidikan Biologi FKIP Unpatti, 2019)
Background: Quantum learning model is a set of learning models that are proven to be effectively applied in schools. This study aims to determine the application of biological learning devices using quantum learning models to the learning outcomes of virus material can improve student learning outcomes in class X SMA Kartika XIII-1 Ambon. Method: This type of research is descriptive type. The population in this study is SMA Kartika XIII-1 Ambon. The samples in this study were all students of class X MIA SMA Kartika XIII-1 Ambon, amounting to 16 students. The data obtained were analyzed descriptively and inferentially. Results: In the cognitive aspect of 16 students there were 5 students with a percentage (31.25%) getting grades (85-100) with very good qualifications and 11 students with a percentage (68.75%) getting grades (77-84) with qualifications well. Affective aspects, where at intervals of 77-84 there are 13 students (81.25%), 3 students score at intervals of 70-76 (18.75%) who have this value with complete qualifications. Psychomotor aspects, where at intervals of â‰¥70 there are 16 students (100%) who have grades with complete qualifications. Conclusion: The level of student success viewed from cognitive, affective, and psychomotor aspects. This is in accordance with the analysis data and the percentage data obtained at the initial test was 65.31% while the final percentage of the test produced was 79.68%.